B-Cell Epitope Mapping of TprC and TprD Variants of Treponema pallidum Subspecies Informs Vaccine Development for Human Treponematoses - Molini, Barbara; Fernandez, Mark C.; Godornes, Charmie; Vorobieva, Anastassia; Lukehart, Sheila A.; Giacani, Lorenzo (Frontiers in Immunology, 2022)
Several recent studies have focused on the identification, functional analysis, and structural characterization of outer membrane proteins (OMPs) of Treponema pallidum (Tp). The Tp species encompasses the highly related pallidum, pertenue, and endemicum subspecies of this pathogen, known to be the causative agents of syphilis, yaws, and bejel, respectively. These studies highlighted the importance of identifying surface-exposed OMP regions and the identification of B-cell epitopes that could be protective and used in vaccine development efforts. We previously reported that the TprC and TprD OMPs of Tp are predicted to contain external loops scattered throughout the entire length of the proteins, several of which show a low degree of sequence variability among strains and subspecies. In this study, these models were corroborated using AlphaFold2, a state-of-the-art modeling tool. Here, we identified B-cell epitopes across the full-length TprC and TprD variants using the Geysan pepscan mapping approach with antisera from rabbits infected with syphilis, yaws, and bejel strains and from animals immunized with refolded recombinant TprC proteins from three syphilis strains. Our results show that the humoral response is primarily directed to sequences predicted to be on surface-exposed loops of TprC and TprD proteins, and that the magnitude of the humoral response to individual epitopes differs among animals infected with various syphilis strains and Tp subspecies. Rather than exhibiting strain-specificity, antisera showed various degrees of cross-reactivity with variant sequences from other strains. The data support the further exploration of TprC and TprD as vaccine candidates.